Delimitation of cryptic species inside Claviceps purpurea - Pažoutová, Sylvie; Pešicová, Kamila; Chudíčková, Milada; Šrůtka, Petr; Kolařík, Miroslav (Fungal biology, 2015)
Claviceps purpurea is an ovarian parasite infecting grasses (Poaceae) including cereals and forage plants. This fungus produces toxic alkaloids and consumption of contaminated grains can cause ergotism in humans and other mammals. Recent molecular genetics studies have indicated that it included three cryptic species (G1, G2, G3). In this study, reproductive isolation amongst these groups and among material from Phragmites and Molinia was tested using gene flow statistics for five polymorphic loci, and to support these data, phylogenetic affiliations based on gene trees and a multigene phylogeny were used. The four recognized species are characterized based on morphology and host spectrum and formal taxonomic names are proposed. Claviceps purpurea sensu stricto (G1 group) represents a typical rye ergot, but infects various other grasses. Typical hosts of Claviceps humidiphila (new name for G2 species), like Phalaris arundinacea, belong to grasses preferring humid locations. Claviceps spartinae (G3) is specific to chloridoid grasses from salt barches. The material from Phragmites and Molinia can be authenticated with the species Claviceps microcephala for which the new name Claviceps arundinis is proposed here. The divergence time between species was estimated and the tools for species identification are discussed.
Keywords: DNA fungální; Host Specificity; DNA, Fungal; Taxonomy; C. humidiphila; Phylogeny; Sequence Homology; lipnicovité; Sequence Analysis, DNA; Molecular Sequence Data; molekulární sekvence - údaje; Cluster Analysis; C. arundinis; Ergot; C. microcephala; Clavicipitaceae; Molecular clocks; hostitelská specificita; sekvenční analýza DNA; fylogeneze; shluková analýza; Poaceae; Claviceps; sekvenční homologie